Medical Quality Management: Theory And Practice - Varkey, Prathiba (Jones & Bartlett Learning, 2009)
This new comprehensive resource Medical Quality Management: Theory and Practice addresses the needs of physicians, medical students, and other health care professionals for up to date information about medical quality management. In reviewing the key principles and methods that comprise the current state of medical quality management in U.S. health care, this text provides a concise summary of quality improvement, patient safety and quality measurement methodologies. This textbook also describes the current state of global networks and computing technologies, and provides an overview of ethics, legislation, policy making, accreditation and utilization management techniques as it relates to quality improvement. including general approaches and methods, support systems, regulatory constructs, and common outcomes. Complete with case studies, executive summaries, and figures and tables, this is a necessary guide for all executives and medical directors, academicians and students, as well as all physicians and other health professionals in clinical practice.